Bio-Control Potential of Trichoderma harzianum and Beauveria bassiana against Alternaria solani in Tomatoes (Solanum lycopersicum) - Emmy, Cheruiyot; Lizzy , Mwamburi; Billy , Makumba (African Journal of Education,Science and Technology (AJEST), 2024)
In recent years, there has been a growing demand for sustainable and environmentally friendly methods to control pests and diseases in agriculture. This study focused on exploring the potential of Trichoderma harzianum and Beauveria bassiana, both isolated from Moiben-Kenya, as biological agents for controlling Alternaria solani, a tomato pathogen. In-vitro antagonism tests were conducted using dual culture technique and the impact of culture filtrates were also examined. Potency of volatile organic compounds was evaluated using the inverted plate technique. In dual culture, T. harzianum reduced the growth of A. solani by 48.7% while the culture filtrate did not show any effect. The inhibitory effect of B. bassiana culture filtrates was dose-dependent, with a 5% concentration achieving 8% inhibition, a 10% concentration registering 33% inhibition, and a 15% concentration achieving 39% inhibition. Volatile organic compounds released by T. harzianum inhibited A. solani colonies by up to 50%, while B. bassiana reached a maximum inhibition of 30%. The biocontrol agents were able to exert varying levels of biocontrol towards the test pathogen. It is recommended that in vivo studies be done to assess the application of the biocontrol agents under study in field conditions.